Watershed development inputs and social change : understanding the changing culture of child nutrition - Pandit, Apoorvaa; Watershed Organisation Trust (Ahmednagar, India) (Ahmednagar : Watershed Organisation Trust ; Jaipur : Rawat Publications, 2010)
The study is conducted in the villages, viz., Mhaswandi, Kangar, and Kalas Pimpri of Ahmednagar District.
Includes bibliographical references (p. [163]-165) and index.
Keywords: Watershed management -- Social aspects -- India -- Ahmadnagar (District); Children -- Nutrition -- India -- Ahmadnagar (District)